Physical proximity and occupational employment change by gender during the COVID-19 pandemic - Jacqueline Mosomi; Amy Thornton (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Previous economic downturns such as the 2008-09 Global Financial Crisis disproportionately affected male employment due to greater contractions in industries typically filled by men (e.g., manufacturing). However, after the imposition of the 'hard' COVID-19 lockdown between 2020 quarter 1 and 2 in South Africa, both men and women lost about a million jobs. We show a higher ratio of female-to-male job loss in the 2020 recession compared to 2008- 09 is partly explained by South African women's clustering in occupations high in physical proximity (e.g., services). South African labour market data are combined with occupational work context data from O*NET to show that employment change between 2020 quarter 1 and 2 (but not 2008 and 2009) is well explained by factors specific to COVID-19 social distancing protocols. Occupations higher in physical proximity, difficult to perform from home, or deemed non-essential by government were most likely to shed jobs.
Keywords: I10; J01; J16; J24; 330; pandemic; COVID-19; occupational sorting; O*NET; physical proximity; work from home; gender